Cell Cycle Arrest and Apoptosis Induction by a New 2,4-Dinitrobenzenesulfonamide Derivative In Acute Leukemia Cells - Patricia Alves Almeida; Luiz Felipe Schmitz de Souza; Mariana Franzoni Maioral; Laura Otto Walter; Bruna Fischer Duarte; Íris Mattos Santos-Pirath; Douglas Bauer Speer; Larissa Sens; Tiago Tizziani; Aldo Sena de Oliveira; Ricardo José Nunes; Maria Cláudia Santos-Silva (Frontiers Media S.A., 2021)
Background: Current therapies for acute leukemias (ALs) are associated with severe adverse reactions and high relapse rates, which makes the search for new antileukemic agents a necessity. Therefore, the aim of this study was to evaluate the effects of a new sulfonamide, S1, in AL cells K562 and Jurkat. Methods: The cytotoxic activity of S1 was assessed using MTT method. The involvement of apoptosis in the mechanism of cell death was assessed by flow cytometry and fluorescence microscopy. Results: Our results demonstrated that S1 induced morphological changes suggestive of apoptosis in both K562 and Jurkat cells. Additionally, S1 was not cytotoxic to normal erythrocytes and mononuclear cells and had a highly selective cytotoxicity for AL lineages. The mechanisms of cell death induced by S1 in K562 cells involves cell cycle arrest at G2/M phase and the activation of both extrinsic and intrinsic apoptosis, with an increased FasR and AIF expression and the loss of mitochondrial potential. As for Jurkat, we observed cell cycle blockade at G0/G1 phase, phosphatidylserine exposure and the involvement of intrinsic apoptosis only, with mitochondrial potential loss and a reduced expression of Survivin.  Although sulfonamide S1 did not altered Bcl-2 and Bax expression in AL cell lines, it was able to activate caspase-3 in K562 cells. Conclusion: Our results suggest that sulfonamide S1 may be a promising candidate for the development of new drugs for the treatment of ALs